2014
DOI: 10.3109/17435390.2014.958116
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of silver nanoparticles in the rat lung: Influence of dose, size, and chemical composition

Abstract: Increasing silver nanoparticle (AgNP) use in sprays, consumer products and medical devices has raised concerns about potential health effects. While previous studies have investigated AgNPs, most were limited to a single particle size or surface coating. In this study, we investigated the effect of size, surface coating and dose on the persistence of silver in the lung following exposure to AgNP. Adult male rats were intratracheally instilled with four different AgNPs: 20 or 110nm in size and coated with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
7
40
0
Order By: Relevance
“…The polydispersity index, a measure of the variance in mean hydrodynamic diameter measurements, was 0.15 ± 0.01 for citrate-coated AgNPs and 0.2 ± 0.01 for PVP-coated AgNPs. These analyses indicated AgNPs of the expected size and a narrow size distribution, consistent with other studies using the same AgNPs (Anderson et al, 2015; Wang et al, 2014). …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The polydispersity index, a measure of the variance in mean hydrodynamic diameter measurements, was 0.15 ± 0.01 for citrate-coated AgNPs and 0.2 ± 0.01 for PVP-coated AgNPs. These analyses indicated AgNPs of the expected size and a narrow size distribution, consistent with other studies using the same AgNPs (Anderson et al, 2015; Wang et al, 2014). …”
Section: Resultssupporting
confidence: 90%
“…Likewise, Ag levels were not significantly different in the lungs of rats at 1 day after intratracheal instillation of citrate- and PVP-coated AgNPs (Anderson et al, 2015). However, Ag levels at 21 days post-exposure were 3-fold higher in rats exposed to citrate-coated AgNPs than PVP-coated AgNPs (Anderson et al, 2015). This observation suggested that citrate-coated AgNPs persist in the lung longer than PVP-coated AgNPs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In their study, citrate-coated Ag NPs produced greater and/or longer-lasting effects than PVP-coated ones due to a greater ability of PVP-coated Ag NPs to complex released Ag cations (Ag + ). Previous studies by our group, Anderson and colleagues (2014), using the same materials showed greater clearance of instilled PVP- versus citrate-coated Ag NPs. In accordance with findings by oropharyngeal aspiration (Wang et al , 2013), we hypothesized that nose-only inhalation of C20 would produce greater acute cellular toxicity and neutrophilic inflammation than C110 and that C110 would produce mild sub-chronic pulmonary fibrosis.…”
Section: Introductionsupporting
confidence: 53%
“…Primary size and morphology, hydrodynamic size and electrostatic potential, elemental and Ag + composition, and endotoxin content were determined using transmission electron microscopy (TEM), dynamic light scattering (DLS), inductively coupled plasma mass spectrometry (ICP-MS), and the Kinetic Turbidity and Gel-clot limulus amebocyte lysate (LAL) assays, respectively. Descriptions and results of these characterization methods have been presented previously (Wang et al , 2013, Anderson et al , 2014). …”
Section: Methodsmentioning
confidence: 99%